PERAN MEDIA DIGITAL DALAM MENDUKUNG PROSES PEMBELAJARAN BAHASA INDONESIA - Hia, Lestari Iman Putri; Sarah, Sartika; Yunus, Syarifudin (Sindoro: Cendikia Pendidikan, 2025)
The advancement of digital technology has brought significant changes in the world of education, including in learning Indonesian. Digital learning media, such as interactive videos, e-books, educational applications, and online learning platforms, have been used to improve the effectiveness of the learning process. The use of this media allows for the delivery of more interesting materials, increases students' learning motivation, and provides flexibility in accessing learning resources anytime and anywhere. In addition to these benefits, there are challenges that still need to be overcome, such as limited access to technology, low digital literacy among teachers and students, and the potential for disruption due to uncontrolled use of digital media. Therefore, the use of digital learning media needs to be balanced with the right strategy so that it can have a positive impact on the process of learning Indonesian. Kemajuan teknologi digital telah membawa perubahan signifikan dalam dunia pendidikan, termasuk dalam pembelajaran Bahasa Indonesia. Media pembelajaran digital, seperti video interaktif, e-book, aplikasi edukasi, dan platform pembelajaran daring, telah digunakan untuk meningkatkan efektivitas proses pembelajaran. Penggunaan media ini memungkinkan penyampaian materi yang lebih menarik, meningkatkan motivasi belajar siswa, serta memberikan fleksibilitas dalam mengakses sumber belajar kapan saja dan di mana saja. Selain manfaat tersebut, terdapat tantangan yang masih harus diatasi, seperti keterbatasan akses terhadap teknologi, rendahnya literasi digital di kalangan guru dan siswa, serta potensi gangguan akibat penggunaan media digital yang tidak terkontrol. Oleh karena itu, pemanfaatan media pembelajaran digital perlu diimbangi dengan strategi yang tepat agar dapat memberikan dampak positif dalam proses pembelajaran Bahasa Indonesia.